Pneumoencephalon and pneumatocoele intrabulbaris – the consequence of the penetrating wound of orbital cavity and severe ocular injury – cases report - Brożek, Marzenna; Kaźmierska, Hanna; Bieganowski, Lech (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Pneumoencephalon i.e. the presence of the intracranial air is commonly detected in the consequence of the head injury or penetrating wound of orbital cavity. The most characteristic sign of pneumoencephalon is the bruit hydroaerique, which is a splashing sound heard only by the patient on postural change. The diagnosis of this rare complication was possible on clinical symptoms and computed tomography (CT) brain scan. The article outlines another case of the intraocular presence of the air (pneumatocoele intrabulbaris) after severe ocular injury with almost total absence of vitreous body, choroid and retina and hypotony.